The perception of customers (Celcom, Maxis And Digi) towards service quality of Acision Sdn. Bhd./ Siti Nooraishah Abdul Majid (Faculty of Business and Management, 2007)
This research is about to study on perception of customers towards service quality of Acision Sdn. Bhd. The dimensions such as tangibles, reliability, responsiveness, assurance and empathy have been identified in order to investigate whether or not these factors have an effect towards service quality by using service quality dimensions. Objectives are to determine which elements in service quality need an improvement by Acision Sdn Bhd. And also to identify suggestion to improve service quality provided Acision Sdn. Bhd. The survey is conducted at Klang Valley which the 3 headquarters of networking situated. For example, Celcom in Celcom Tower, Maxis in Maxis Tower and DiGi headquarters' in Jalan Semarak. This is probability research and use simple random sampling to pick up the respondents. The sample size for this study is 60 respondents who are working in 3 networking that available in Malaysia. Data obtained using a method which is primary data and used questionnaires as a technique to collect a data. The Statistical Package for the Social Science (SPSS) version 14.0 will be used to summarize the data. The results will be in form of reliability testing, frequency, mean, percentage and cross tabulation. For overall findings show that the respondents perception agree that Acision Sdn. Bhd. are provided service quality to the customers. FACULTY OF BUSINESS MANAGEMENT UiTM, MELAKA 2007